(untitled) (Comparative Professional Pedagogy, 2023)
The processes of globalization and digitalization of society and the pandemic necessitated significant changes in education. The system of higher education in Ukraine, which strives to get closer to European standards, is adapting to new realities in the extremely difficult conditions of wartime. Studying the experience of the Republic of Turkey, which is actively participating in the Bologna process, and its potential for adaptation to modern challenges are becoming more and more relevant for our country. The aim of the research is to analyze the structure of higher education in the Republic of Turkey, and the peculiarities of its functioning within the framework of European Integration. Further comparing it with the higher education system in Ukraine and identifying advantageous practices will provide ways to improve the organization and content of the Ukrainian higher education system. The article examines the main aspects of the higher education system in Turkey. Different types of educational institutions are considered. Their purpose, structure, duration of study, degrees, and qualifications were analyzed. Peculiarities of state and private universities are studied. The degree of autonomy of public and private universities in the formation of their mission and educational philosophy, sources of their funding, and availability of financial support from the state are compared. The role of international accreditation of programs as a means of increasing the reputation of universities as well as attracting foreign students and teachers is defined. It is noted that internationalization is becoming more and more relevant for higher education in Turkey, which is reflected in exchange programs, double degrees, and the involvement of foreign students and teachers. The reasons for the different intensity of scientific research in state and private universities are analyzed. Attention is drawn to the partnerships of universities with industry organizations for the implementation of joint applied research projects focused on the specific needs of the industry. It was concluded that the priority for the further development of higher education in Turkey is training of qualified scientific and pedagogical staff.